RELATIONSHIP BETWEEN RECURRENT APHTHOUS STOMATITIS WITH IRON DEFICIENCY ANEMIA: HUBUNGAN ANTARA STOMATITIS AFTOSA REKUREN DENGAN ANEMIA DEFISIENSI BESI - Nurdiana, Nurdiana; Astari, Pocut (Dentika: Dental Journal, 2018)
Recurrent aphtous stomatitisis a recurrent oral ulcer. Clinically recurrent aphtous stomatitis is easy to diagnose, but its etiology and pathogenesis remain unclear because it has no single or specific cause. The main predisposing factors associated with recurrent aphtous stomatitis are genetic factors, hematological and immunologic abnormalities, local factors such as trauma, and smoking cessation. Several studies have shown that hematological abnormalities can affect the oral mucosa and cause recurrent aphtous stomatitis. The purpose of this study was to examine the relationship between recurrent aphthous stomatitis and iron deficiency anemia, as well as the relationship between recurrent aphthous stomatitis and hematological status. The subjects consist of 59 recurrent aphtous stomatitis patients and 60 control patients. A full blood examination was carried out for all subjects. Hemoglobin level, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and serum iron level are determined for each subject.The result of this study showed that there is no significant difference in hemoglobin level, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and serum iron level with p-value of 0.714, 0.395, 0.809, 0.497, and 0.368, respectively. The result also showed that there is no significant difference in iron deficiency anemia status between the recurrent aphtous stomatitis and control group (p = 0,7). Therefore, it can be concluded that there is no relationship between iron deficiency anemia and recurrent aphtous stomatitis incidence.